Biomechanics of skeletal fracture fixation and spine structure - Krishna Kotlanka Rama (2008)
This dissertation is on ‘biomechanical optimization analysis of bone-fracture fixation and spinal unit’s structures of the vertebral body and intervertebral disc’. Biomechanical optimal analysis of bone-fracture fixation involves (i) determination of optimal plate geometry (ii) demonstration of stiffness-graded plates causing less stress-shielding and (iii) use of helical plates for transverse fracture and for improved plate-bone holding capacity. Biomechanical optimal analysis of the spinal vertebral body (VB) and intervertebral disc (IVD) demonstrates (i) how the VB transmits all types of loading as axial forces through its cortex, to demonstrate its inherent design as a high-strength light-weight structure, (ii) how the IVD effectively contains deformation with increasing level of applied forces, because of the role of the nucleus pulposus in stressing the annulus and raising its elastic modulus, so that nucleotomy (wherein the nucleus pulposus is removed) is a contra-indication for the ruptured disc.